2019
DOI: 10.1016/j.eururo.2018.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox B13 G84E Mutation and Prostate Cancer Risk

Abstract: Background The homeobox B13 ( HOXB13 ) G84E mutation has been recommended for use in genetic counselling for prostate cancer (PCa), but the magnitude of PCa risk conferred by this mutation is uncertain. Objective To obtain precise risk estimates for mutation carriers and information on how these vary by family history and other factors. Design, setting, and participants Two-fold: a systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
(94 reference statements)
0
23
1
1
Order By: Relevance
“…The screening of the HOXB13 gene is recommended for men who develop an early‐onset and/or familial Pca 11 . Nowadays, the HOXB13 gene is included on the standard laboratory Pca Panel 20 . A recent meta‐analysis of the Pca risk for HOXB13 G84E has shown that the risk of Pca for carriers varies by Pca family and by birth cohort 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The screening of the HOXB13 gene is recommended for men who develop an early‐onset and/or familial Pca 11 . Nowadays, the HOXB13 gene is included on the standard laboratory Pca Panel 20 . A recent meta‐analysis of the Pca risk for HOXB13 G84E has shown that the risk of Pca for carriers varies by Pca family and by birth cohort 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the HOXB13 gene is included on the standard laboratory Pca Panel 20 . A recent meta‐analysis of the Pca risk for HOXB13 G84E has shown that the risk of Pca for carriers varies by Pca family and by birth cohort 20 . Regarding the allele frequency of the HOXB13 c.853delT variant observed in the Pca cohort, it will be necessary to assess relative and absolute Pca risks for HOXB13 c.853delT carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity of measured HOXB13 G84E mutation risk across distinct studies might result as a function of differing carrier proportions of adjacent and untested locus sentinels. This is likely to be correlated with study population characteristics such as family history, age of diagnosis, and pathologic severity 6 , and should be considered with further studies.…”
Section: Discussionmentioning
confidence: 96%
“…HOXB13 G84E was subsequently confirmed as a moderate penetrance PrCa susceptibility variant in European ancestry populations through a number of independent studies, with consistent evidence demonstrated for strong associations with early-onset and familial PrCa, but importantly no evidence for increased risk of poorer prognosis disease in mutation carriers [ 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]. HOXB13 G84E mutations are estimated to be present in up to 5% of European ancestry families with hereditary PrCa [ 140 ], whilst average estimated risks of developing PrCa for heterozygous male carriers are approximately 17% by age 65 rising to 62% by age 85, and further increasing with stronger family history of PrCa [ 141 ]. The HOXB13 G84E mutation is found almost exclusively in European ancestry populations [ 131 , 132 , 133 , 140 , 142 ].…”
Section: Initial Approaches For the Identification Of Prca Susceptmentioning
confidence: 99%